2021
DOI: 10.1111/jpn.13542
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and rumen morphometrics of Nellore and ½ Angus/Nellore feedlot cattle adapted over 9 and 14 days to high‐concentrate diets

Abstract: The objective of this study was to evaluate the effects of adapting Nellore and ½ Angus/Nellore (AN) feedlot cattle over periods of 9 and 14 days to high‐concentrate diets on performance, feeding behaviour, carcass traits and rumen morphometrics. Seventy‐two yearling bulls (313.5 kg ± 24.5), 36 Nellore and 36 AN, were randomly allocated in 24 pens (3 animals/pen; 24 m2 and 2.0 m of bunk space/animal) according to a randomized complete block design with a 2 × 2 factorial arrangement of treatments as follows: Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several studies were conducted previously to determine the most appropriate adaptation period for Nellore cattle receiving high-concentrate diets in Brazilian feedlots (Estevam et al, 2020;Watanabe et al, 2022), and authors reported that Nellore cattle should not be adapted in less than 14 days. However, in all of these studies, the cattle went through a ten-day receiving period, where they consumed a forage-based diet ad libitum to standardize the ruminal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted previously to determine the most appropriate adaptation period for Nellore cattle receiving high-concentrate diets in Brazilian feedlots (Estevam et al, 2020;Watanabe et al, 2022), and authors reported that Nellore cattle should not be adapted in less than 14 days. However, in all of these studies, the cattle went through a ten-day receiving period, where they consumed a forage-based diet ad libitum to standardize the ruminal microbiota.…”
Section: Introductionmentioning
confidence: 99%